Expression Patterns in Reductive Iron Assimilation and Functional Consequences during Phagocytosis of Lichtheimia corymbifera, an Emerging Cause of Mucormycosis - Felicia Adelina Stanford; Nina Matthies; Zoltán Cseresnyés; Marc Thilo Figge; Mohamed I. Abdelwahab Hassan; Kerstin Voigt (Journal of Fungi, 2021)
Iron is an essential micronutrient for most organisms and fungi are no exception. Iron uptake by fungi is facilitated by receptor-mediated internalization of siderophores, heme and reductive iron assimilation (RIA). The RIA employs three protein groups: (i) the ferric reductases (Fre5 proteins), (ii) the multicopper ferroxidases (Fet3) and (iii) the high-affinity iron permeases (Ftr1). Phenotyping under different iron concentrations revealed detrimental effects on spore swelling and hyphal formation under iron depletion, but yeast-like morphology under iron excess. Since access to iron is limited during pathogenesis, pathogens are placed under stress due to nutrient limitations. To combat this, gene duplication and differential gene expression of key iron uptake genes are utilized to acquire iron against the deleterious effects of iron depletion. In the genome of the human pathogenic fungus L. corymbifera, three, four and three copies were identified for FRE5, FTR1 and FET3 genes, respectively. As in other fungi, FET3 and FTR1 are syntenic and co-expressed in L. corymbifera. Expression of FRE5, FTR1 and FET3 genes is highly up-regulated during iron limitation (Fe-), but lower during iron excess (Fe+). Fe- dependent upregulation of gene expression takes place in LcFRE5 II and III, LcFTR1 I and II, as well as LcFET3 I and II suggesting a functional role in pathogenesis. The syntenic LcFTR1 I–LcFET3 I gene pair is co-expressed during germination, whereas LcFTR1 II- LcFET3 II is co-expressed during hyphal proliferation. LcFTR1 I, II and IV were overexpressed in Saccharomyces cerevisiae to represent high and moderate expression of intracellular transport of Fe3+, respectively. Challenge of macrophages with the yeast mutants revealed no obvious role for LcFTR1 I, but possible functions of LcFTR1 II and IVs in recognition by macrophages. RIA expression pattern was used for a new model of interaction between L. corymbifera and macrophages.